Promoting Positive Discipline in Developing Love for Reading Using Comprehensive Analytical Reading Inventory (CARI): A Review Study - Alpapara, Loren S. (Bumi Publikasi Nusantara, 2022)
The reading performance of Grade Seven Students at Palapas National High school is low as reflected in the Pre Reading-Assessment conducted last May 2019. 48 students out of 136 were considered under frustration level. This study focused on the effectiveness of remedial reading to the students with learning disabilities in reading at Palapas National High School. It aimed to promote positive discipline in developing a love for Reading used in the conduct of remedial reading. It covered 48 students from Grade Seven as the respondents. They were composed of 29 males and 19 females. The research investigated the reading level of the respondents and the significant difference after the intervention. This study is a pretest and posttest experimental design. The total enumeration method was utilized, where all the grade seven were measured individually in terms of their reading skills to determine who among them was categorized under nonreader, frustration level, instructional, and independent. The findings indicated an increase from the results of the pretest to the posttest. The result of the posttest based on computed mean which is 30.1 as their reading level was found significantly higher than the pretest result which is 21.5. It is recommended that the conduct of remedial reading classes should be implemented consistently for the students to develop positive discipline in developing a love for reading, supported by varied instructional materials and appropriate teaching strategies.